The measurement of mechanical parameters of a switched reluctance motor drive system - Gobbi, R.; Sahoo, N. C.; Vejian, R. (IOP PUBLISHING LTD, 2007)
The switched reluctance motor has been receiving attention recently after the availability of power electronics devices, for its robustness, simple construction and a high torque/mass ratio. The electromagnetic characteristic measurement for the motor has been widely researched and reported despite nonlinear behavior of the motor. The electromagnetic characteristic data are being used as look-up tables for modeling and simulation purposes. However, for dynamic simulation, mechanical parameters such as friction coefficients and moment of inertia are equally important. There has not been much work done to measure the parameters as mostly they are provided by the manufacturer of mechanical parts ( the motor etc) which are not accurate for the entire mechanical system, when they are coupled. A few measurement methods have been used widely to measure the mechanical parameters but the important friction constants such as Coulomb friction constant were neglected. This paper introduces a new technique which was derived from the classical viscous plus Coulomb friction model for all the mechanical parameter measurements including the Coulomb friction. The results obtained were verified using experimental data.